2022
DOI: 10.1111/trf.17007
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of national blood conservation recommendations at an adult sickle cell center

Abstract: Background Due to the national blood supply crisis caused by the COVID‐19 pandemic, the American Society of Hematology proposed guidance to decrease blood utilization for sickle cell patients on chronic transfusion therapy (CTT). Little evidence exists to support the efficacy and safety of these blood conservation strategies. Study Design and Methods Through retrospective analysis, we sought to describe outcomes following implementation of these recommendations in 58 adult sickle cell patients on chronic excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This retrospective crossover analysis of nine patients aims to add to the existing literature on IHD-RCE and address the equipoise regarding whether the benefits of decreased RBC usage per exchange and lower FCR/increased interprocedure interval can be observed at the same time, in the same patient. Our study also provides additional safety data on potentially higher-risk conditions, using greater Hct decreases than reported elsewhere, 3,5,6 while using normal saline replacement exclusively.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…This retrospective crossover analysis of nine patients aims to add to the existing literature on IHD-RCE and address the equipoise regarding whether the benefits of decreased RBC usage per exchange and lower FCR/increased interprocedure interval can be observed at the same time, in the same patient. Our study also provides additional safety data on potentially higher-risk conditions, using greater Hct decreases than reported elsewhere, 3,5,6 while using normal saline replacement exclusively.…”
Section: Introductionmentioning
confidence: 67%
“…Given the challenges of the pandemic, there has been increasing interest in how we can optimize blood utilization in SCD while continuing to maintain appropriate therapeutic goals. 2,3 A recent survey of RCE practice indicated that 40% of respondents use IHD 4 ; as more centers consider adopting this practice, they will need to have a clear, realistic understanding of how much benefit to expect. This retrospective crossover analysis of nine patients aims to add to the existing literature on IHD-RCE and address the equipoise regarding whether the benefits of decreased RBC usage per exchange and lower FCR/increased interprocedure interval can be observed at the same time, in the same patient.…”
Section: Introductionmentioning
confidence: 99%
“…By allowing for a higher FCR, the patient will require fewer donated RBCs. In this month's issue of TRANSFUSION , the study by Jones et al provides evidence that using depletion/exchange and tolerating a higher FCR, while being mindful of patient comorbities, likely does not have a significant clinical impact on sickle cell patients who are compliant with their scheduled regimen 20 . In addition, because the replacement fluid volume typically needed for the depletion is low relative to total plasma volume (about 6%), in some patients, the use of normal saline instead of 5% albumin can be considered while still meeting therapeutic targets 21 …”
mentioning
confidence: 99%
“…Jones et al 20 demonstrated that increased use of depletion/exchange and increasing the FCR resulted in the conservation of over 850 units of RBCs at their center and caused no clinically significant changes to targeted laboratory parameters. For the five patients who transitioned to simple transfusion, there was an increase in the HgbS fraction along with increased anemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation